Three-dimensional printing for restoration of the donor face: A new digital technique tested and used in the first facial allotransplantation patient in Finland. Issue 12 (December 2016) - Mäkitie, A.A.; Salmi, M.; Lindford, A.; Tuomi, J.; Lassus, P.
Summary: Background and aims: Prosthetic mask restoration of the donor face is essential in current facial transplant protocols. The aim was to develop a new three-dimensional (3D) printing (additive manufacturing; AM) process for the production of a donor face mask that fulfilled the requirements for facial restoration after facial harvest. Materials and methods: A digital image of a single test person's face was obtained in a standardized setting and subjected to three different image processing techniques. These data were used for the 3D modeling and printing of a donor face mask. The process was also tested in a cadaver setting and ultimately used clinically in a donor patient after facial allograft harvest. Results: and Conclusions: All the three developed and tested techniques enabled the 3D printing of a custom-made face mask in a timely manner that is almost an exact replica of the donor patient's face. This technique was successfully used in a facial allotransplantation donor patient.